Kakawin Kumudawati : Analisis Intertektualitas - Dwi Mahendra Putra; I Putu Permana Mahardika; Ni Made Ari Dwijayanthi; Ni Made Ayu Susanthi Pradnya Paramitha (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2021)
Kakawin Kumudawati narratively contains Tantri stories. Tantri as a treasure that is very popular in Bali so it is not surprising that Tantri continues to be transformed into various forms of literary genres. Kakawin Kumudawati tells one of the part of stories in the Tantri story, namely the “angsa” and “empas”. Kakawin Kumudawati is a unique work in terms of narrative content, which is built on characters who are husband and wife. Tantri texts have been copied into various literary genres. It is very interesting to study mainly from the source of story writing, so tracking the hypogram is very necessary. Intertextual provides an illustration that the text is present through the reading of other texts both as a mosaic trail and full transformation.Kakawin Kumudawati's primary hypogram is Tantri Carita. The matrix that is determined is manah “mind” which builds the satya model of 'loyalty' which is translated as Panca Satya. In intertextual comparison, Kakawin Kumudawati fulfills three main concepts (1) expansion, (2) conversion, and (2) expression, while (3) modification is not found in Kakawin Kumudawati.